Unexpected results of a nationwide, treatment-independent assessment of fecal incontinence in patients with anorectal anomalies - Schmiedeke, Eberhard; Zwink, Nadine; Holland-Cunz, Stefan; Jenetzky, Ekkehart (Pediatric surgery international, 2012)
Purpose: To determine the anorectal function in patients with anorectal malformations (ARM) in order to facilitate patient counseling and follow-up.MethodsData were collected by the German network for urorectal malformations (CURE-Net) according to the International Krickenbeck consensus. Questionnaires on bowel function and a defecation protocol were completed by the families/patients. The clinical findings were assessed from the patients’ clinical records. Results: Two hundred and ninety-seven patients with ARM were assessed, 175 patients gave complete data on continence, 52 of them were excluded due to mental retardation, age, and earlier type of pullthrough. Complete continence was found in 27 %, perineal fistula in 40 %, rectourethral/vesical in 10 %, vestibular in 24 %, cloaca in 0 %. Krickenbeck grade 1 soiling: 42 %, grade 2 and 3: 31 %. Forty-nine percent of the incontinent patients practiced bowel management, reaching continence in 19 %. The statement of constipation (67 %) was validated with the last clinical findings, showing coprostasis in 46 %, “Not suffering constipation” was confirmed in 61 % and falsified in 29 %.ConclusionARM patients in Germany, as assessed by independent researchers, show a high rate of fecal incontinence and insufficiently treated constipation. Parents should be counseled accordingly and motivated to engage in consequent follow-up. Intensified efforts in the conservative treatment of constipation and fecal incontinence are crucial to improvement.
Gesehen am 05.06.2018